European physico-theology (1650-c.1760) in context celebrating nature and creation - Greyerz, Kaspar von 1947- (Oxford University Press, 2022)
Physico-theology celebrated the observation of nature as a way toward recognising God as Creator, demonstrating the compatibility of the biblical record with new science. This is an English-language monograph which studies the impact of physico-theology on the intellectual and socio-cultural establishment in Europe from the mid-17th century
This edition also issued in print: 2022. - Includes bibliographical references and index
Keywords: Geschichte 1650-1760; God / Proof, Teleological; Nature / Religious aspects / Christianity; Creation; Theology / Europe / History / 18th century; Theology / Europe / History / 17th century; Schöpfungslehre; Natürliche Theologie; Wissenschaft; Europa